“He / looks into / his own eyes”: Thom Gunn’s Ekphrastic Poems - Horváth, Imre Olivér (Hungarian Journal of English and American Studies, 2022)
Thom Gunn’s oeuvre spanned more than four decades, during which he kept writing ekphrastic poems. The way words and images relate to each other in them, however, changed gradually and considerably. While his early work is characterized by the dominance of the verbal over the visual, his later poems from the 1970s and 80s question the dominance of language and attribute destructive power to the image. Word and image become reconciled in Gunn’s last two collections from the 1990s and 2000s, respectively. The gradual change in Gunn’s ekphrastic work corresponds to the development of his identity as a gay man; this identity, full-blown at the end of his career, is reflected in his mature treatment of images. (IOH)